A participação do Conselho de Escola na gestão escolar: a importância do diálogo na atuação dos conselheiros escolares - Ganzella Mota, Michela Fernanda (2024)
Throughout history, the culture of a society is revealed through practices, values and symbolic systems that influence the manifestation of thought expressed through language. Based on this concept, this research has the general objective of analyzing the participation of school counselors in the management of public schools, with the specific objective of analyzing the dialogue of school counselors within the scope of the School Council (CE) in order to understand the implementation process effective democratic management of the school unit. Therefore, it is important to consider the short time it took to create the CE as a space for collective action among actors in the educational scenario, the quality of interactive dialogue (Gohn, 2000), the awareness of the political and administrative reality of school education in the work of school counselors , as well as the organizational structure of this collegial body that has defined purposes and hierarchy in the management of the educational institution standardized and controlled by government legislation in which school counselors collaboratively exercise deliberative, consultative, supervisory, mobilizing and pedagogical functions. Thus, by questioning how dialogue takes place in the work of school counselors in EC meetings, this investigation seeks to understand the dynamics of the historical, political, cultural and social reality of participation in school management. In this context, a theoretical assumption favorable to democratic, participatory and civic-minded school management could be true dialogue based on the concepts of Bohm (1992, 2005). After collecting information from the CE of a school community located in Araraquara, in the interior of the State of São Paulo, the mediations recorded in 11 meeting minutes and the dialogue interactions in the work of school counselors were analyzed. The triangulation of the results of this information led to the units of analysis of the expression of literal thought and the expression of participatory thought, in which the shared meanings, which can favor communication and the suspension of assumptions of the meeting participants, point to factors such as the lack of attentive listening and the hierarchy of power in the decision-making process. The interconnection of literal and participatory thinking endorses the hypothesis that the theory of true dialogue can become a significant tool to enable consensus and collective decisions in EC meetings. In this sphere, this concept of dialogue can contribute to democratic participation in school management, and can favor cultural, political and social training, as well as with the functions, especially the pedagogical one, of the CE, and can promote a new paradigm in the work of school counselors. Furthermore, open new possibilities for studies on democratic participation and dialogue in the areas of Human and Social Sciences.